The unprecedented surge in mumps cases; time to think about vaccination in Nepal? - Twanabasu, Sajal; Homagain, Sushan; Tuladhar, Sucharita; Mahaseth, Ashika; Rijal, Ram Chandra; Maskey, Sujina; Regmi, Dinesh; Subedi, Bhusan Kumar (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Mumps is a self-limiting, common vaccine preventable viral disease characterized by fever and swelling of the unilateral or bilateral parotid gland. . Nepal has not included mumps containing vaccines in the national immunization schedule and hence there are occasional outbreaks but the actual incidence is not known. We are trying to represent the burden of mumps in Nepal by reporting the cases visiting our center during the recent outbreak. Method: This is a cross sectional study conducted at Dhading hospital for the period of 3 months from 15th of May 2023 to 14th of July 2023. All children that presented to pediatric OPD with age less than 14 years of age with symptoms of fever and parotid swelling were included in the study. Follow up was done after 5 days of presentation or immediately if any complications were noticed. Diagnosis of mumps was done clinically using Centers for Disease Control and Prevention (CDC)’s criteria. The data was analyzed using Microsoft Excel 2016. Result: Out of 1875 outpatients, 124 (6.61%) were diagnosed as mumps among which67 (54.03%) were male. Mean age of the patient was 5.9 years (±1.71SD). All the patients complained of fever and swelling of the cheek with abdominal pain 10 (8.06%) as predominant additional symptom. All the patients presented at the pediatric outpatient clinic and none of the cases developed complications. Conclusion: The burden of mumps is underestimated in Nepal due to lack of surveillance and documentation as it is not a notifiable disease.. It is evident that mumps pose a significant disease burden in Nepal and hence mumps vaccine should be considered in national immunization programme.